Plasma-activated water modulates taxanes production and phenylalanineammonia-lyase activity in Taxus baccata cell culture - Mojan Haji Fathali Tehrani; Mohtaram Mahmoudieh; Meisam Zargar; Mohammad Hossein Mirjalili; Mahsa Bamneshin; Mohammad Reza Naghavi (PLoS ONE, 2025)
Paclitaxel, an anti-cancer compound from the Taxus baccata L. (yew tree), is limited in availability from natural sources. This study explores the use of plasma-activated water (PAW) as an elicitor in T. baccata suspension cell cultures to enhance the production of paclitaxel and its precursor, 10-Deacetylbaccatin III (10-DAB III). The effects of PAW on various factors, including fresh and dry weight, cell viability, and phenylalanine ammonia-lyase (PAL) activity were investigated. The PAW treatment was conducted at different concentrations (200, 300, and 400 μL), with a pH of 5.6 to 5.8, and was applied at different time points (0, 7, 14, and 21 days). The results revealed that 10-DAB III was increased (14.04 µg/g) significantly at a concentration of 400 μL of PAW on day 21. In contrast, the highest paclitaxel content (3.342 µg/g) was achieved in the control group on day 21. The PAW treatment reduced cell viability by 32.25% compared to day 0 (86.25%), and PAL activity increased initially before declining, but remained higher than in the control group. This study is the first to demonstrate the potential of PAW to enhance taxanes production in T. baccata cell cultures, warranting further investigation into the underlying mechanisms.